1970
DOI: 10.1203/00006450-197007000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition with Early Treatment of Phenylketonuria

Abstract: ExtractThirty-two children with phenylketonuria in whom dietary therapy was started prior to 6 months of age are reviewed. Evidence of profound malnutrition during year 1 of life, demonstrated by deficient growth, anemia, hypoproteinemia, roentgenographic bone changes, and various clinical symptoms, was found in three patients. In two of these patients, the malnutrition was quickly corrected; present intelligence levels in these patients are dull normal. The third patient, however, suffered prolonged malnutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Too low a level leads to a deficiency syndrome which is likely to be as harmful to intellectual development as a prolonged high phenylalanine level (Umbarger el al., 1965;Rouse, 1966;Hanley et al, 1970;Hunt et al, 1971). Such a deficiency of phenylatanine leads to lethargy and refusal to eat and the patient develops a lever of undetermined origin.…”
Section: Considerations In the Dietary Treamaent Of Phenyiketonuriamentioning
confidence: 95%
“…Too low a level leads to a deficiency syndrome which is likely to be as harmful to intellectual development as a prolonged high phenylalanine level (Umbarger el al., 1965;Rouse, 1966;Hanley et al, 1970;Hunt et al, 1971). Such a deficiency of phenylatanine leads to lethargy and refusal to eat and the patient develops a lever of undetermined origin.…”
Section: Considerations In the Dietary Treamaent Of Phenyiketonuriamentioning
confidence: 95%
“…In each of these cases, the authors believed that they were treating children who did in fact have some form of PKU; it is likely that some of these children had variant forms of abnormal phenylalanine metabolism. We did not identify any case reports after 1970 of adverse medical events related to identification and treatment of children with PKU, though in 1970 Hanley et al reported still having considerable difficulty in balancing the nutritional needs of the growing infant with the need to keep phenylalanine levels low [Hanley et al, 1970]. Of 32 children in whom dietary treatment for PKU was started before six months of age, six had IQs less than 75 by age five year.…”
Section: Phenylketonuriamentioning
confidence: 45%
“…It has been difficult in our experience to achieve consistent levels this low. In fact, Hanley et al [4] in 1970 published data suggesting that very stringent control may be harmful and result in hypophenylalaninemia, growth retardation and decreased intelligence. In looking at Fig.…”
Section: Discussionmentioning
confidence: 99%